Efficient and readily tuneable near-infrared photodetection up to 1500 nm enabled by thiadiazoloquinoxaline-based push–pull type conjugated polymers. Issue 29 (8th July 2020) - Verstraeten, Frederik; Gielen, Sam; Verstappen, Pieter; Raymakers, Jorne; Penxten, Huguette; Lutsen, Laurence; Vandewal, Koen; Maes, Wouter
Abstract : Organic photodetectors made from thiadiazoloquinoxaline-based copolymers reach high detectivities in the near-infrared range up to 1400 nm. Abstract : The majority of bulk heterojunction near-infrared organic photodetectors (NIR-OPDs) have an absorption window up to 1000 nm (1.2 eV) due to the scarcity of suitable NIR-absorbing electron donor polymers and the challenging energy alignment and/or blend miscibility with electron acceptor materials, strongly complicating to move beyond this wavelength range. Nonetheless, extension of the detectivity further into the NIR is important for applications such as bio-imaging, pulse oximetry and industrial sorting. Herein, we illustrate that [1, 2, 5]thiadiazolo[3, 4- g ]quinoxaline (TQ) is an excellent building block for the development of ultra-low bandgap copolymers to achieve tuneable NIR photodetection beyond 1000 nm. Three TQ monomers with different side chain patterns are synthesized and combined with carefully selected electron rich subunits to yield push–pull type copolymers with an optical gap ranging from 1.14 to 0.87 eV. The highest gap material affords the best OPD performance, with a peak specific detectivity of 3 × 10 11 Jones at 960 nm (at −2 V bias). The other polymers show <1 eV optical gaps and specific detectivities exceeding 10 10 Jones up to 1400 nm (at −2 V bias). These values are among the highest reported so far for NIR-OPDs in the wavelength range beyond 1000 nm.